Gambaran Korban Meninggal Dunia dengan Cedera Kepala pada Kecelakaan Lalu Lintas di Bagian Forensik RSUP dr M Djamil Padang Tahun 2018-2019 - Muhammad Imam Arrasyid; Rika Susanti; Roza Mulyana (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. A traffic accident is an incident on the road which accidentally involves a vehicle with or without other road users which results in human casualties and/or property loss. The most common injury that occurs during traffic accidents is head injury. Head injury due to traffic accidents is a major cause of disability and mortality in developing countries.Objective. To analyze the overview of victim who died with head injury in traffic accidents at the forensic department of DR. M. Djamil Padang 2018-2019.Methods. This type of research is retrospective descriptive. Sampling was carried out by total sampling technique in the forensic department of RSUP Dr. M. Djamil Padang from March 2020 - September 2020.Results. The results showed that 150 victims who died with head injury in traffic accidents. The conclusion of this study, most of the age is 15-29 years and the incidence was higher in males. The most common injury patterns are abrasions.The head region most affected is the frontalis region. The most time for accidents is at 12.01-18.00 WIB and the most accident days are on Sundays. Most of the accident locations were outside the city of Padang, most types of vehicles were motorbikes, the role of the most victims were motorists and the most types of accidents were being hit by other vehicles.Conclusion. Most of the age is 15-29 years and the incidence was higher in males. The head region most affected is the frontalis region. Most of the accident locations were outside the city of Padang, most types of vehicles were motorbikes, the role of the most victims were motorists and the most types of accidents were being hit by other vehicles